A 10-Year Study of the Impact of Intimate Partner Violence Primary Aggressor Laws on Single and Dual Arrest - Hirschel, Joseph David (Journal of interpersonal violence, 2021)
The adoption of arrest as the preferred response in incidents of intimate partner violence has generally been welcomed, but it has not come without unintended consequences. Foremost among these has been an increase in dual arrest, the situation where both parties to an incident are arrested. To address this concern, many states have enacted primary aggressor laws which mandate that officers determine who is the primary aggressor in the incident. To date, no longitudinal national study has been conducted on the impact of these laws. Using a dataset comprising 10 years of National Incident Based Reporting System (NIBRS) data (2000-2009) from 5,481 jurisdictions in 36 states and the District of Columbia, the authors examine the impact of primary aggressor laws in reducing the prevalence of dual arrests. Taking into account such factors as seriousness of offense, the authors found that the existence of primary aggressor laws does appear to result in officer reluctance to make any arrest. In addition, though these laws do result in a reduction in dual arrests, this reduction was not statistically significant. This is undoubtedly a result of inter-state variation in implementation as well as variations in statutory framework. In addition, these laws were observed to have a disparate effect both on White and non-White and heterosexual and same-sex couples. The policy implications of these findings are discussed.